2006
DOI: 10.1249/00005768-200605001-01768
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Ultrafine and Fine Particulate Matter Disrupts Systemic Vascular Function

Abstract: This study investigated the effects of particulate matter (PM) with aerodynamic diameter 0.02-1 μm (noted as PM 1 ) inhalation during exercise on conduit artery and microvascular function. Inhalation of internal combustion-derived PM is associated with cardiovascular mortality and morbidity. Direct action of PM on the vascular endothelium is likely, as a substantial fraction of ultrafine PM translocates from the alveoli to the circulatory system. Sixteen intercollegiate athletes performed 30 min of exercise wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Therefore, the exposure levels reported in this investigation must be interpreted with caution as they are likely conservative estimates of actual exposures in transportation environments. Nevertheless, the majority of particles produced by gasoline and diesel vehicles are between 0.02 and 0.1 mm in diameter (Morawska and Zhang, 2002), and previous studies employing P-TRAKs have observed significant associations between UFP counts and oxidative DNA damage (Vinzents et al, 2005) as well as changes in heart rate variability (Chan et al, 2004) and vasoconstriction (Rundell et al, 2007). Therefore, while the P-TRAK is not the most sensitive instrument available, it remains a valuable instrument in environmental epidemiology owing to its portability and relatively low cost.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the exposure levels reported in this investigation must be interpreted with caution as they are likely conservative estimates of actual exposures in transportation environments. Nevertheless, the majority of particles produced by gasoline and diesel vehicles are between 0.02 and 0.1 mm in diameter (Morawska and Zhang, 2002), and previous studies employing P-TRAKs have observed significant associations between UFP counts and oxidative DNA damage (Vinzents et al, 2005) as well as changes in heart rate variability (Chan et al, 2004) and vasoconstriction (Rundell et al, 2007). Therefore, while the P-TRAK is not the most sensitive instrument available, it remains a valuable instrument in environmental epidemiology owing to its portability and relatively low cost.…”
Section: Discussionmentioning
confidence: 95%
“…30 Ultrafine particles of aerodynamic diameter 0.1μM are emitted by diesel engines and can pass directly into the blood circulation, limiting oxygen delivery by inducing vasoconstriction, vascular inflammation, and increasing blood viscosity. [30][31][32] Fine particles of 2.5 μM emitted by diesels accumulate within the pulmonary alveoli and cause an inflammatory reaction of the lung that is related both to their physical parameters and the oxidative stress generated by the organic and metallic compounds adsorbed onto their surface. 33 These compounds trigger the local production by macrophages and activated alveolar cells of inflammatory cytokines such as interleukin 6 and tumor necrosis factor α and the potent vasoconstrictor endothelin 1.…”
Section: Air Pollutionmentioning
confidence: 99%
“…This in turn is driven by a constellation of interlinked risk factors. Primary amongst these factors are anemia, [6][7][8][9] diabetic hyperglycemia, [10][11][12] hypertension, [13][14][15][16][17] hypercholesterolemia, [18][19][20] cigarette smoking, [21][22][23][24][25][26][27] air pollution, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] atherosclerosis, [43][44][45][46][47][48][49][50][51][52] repeated episodes of acute kidney injury, [53][54][55][56]…”
mentioning
confidence: 99%
“…2 Of the small number of studies reported (compared with the much larger literature on specific components of traffic emissions), the main cardiorespiratory findings in humans were that short-term exposures can bring about decrements in lung function and enhanced responses to allergens in adult subjects with asthma (Svartengren et al, 2000;McCreanor et al, 2007), as well as positive and negative effects on vascular function in healthy subjects (Rundell et al, 2007;Bräuner et al, 2008). On-road animal studies, utilizing compromised or allergic rodents, observed mild pulmonary inflammation (Elder et al, 2004), significant alterations in lung structure and elastic properties (Mauad et al, 2008), and systemic inflammation and effects on vascular function and autonomic control of the heart (Elder et al, 2004(Elder et al, , 2007.…”
Section: Rationalementioning
confidence: 99%